Electrochemical storage mechanism of sodium in carbon materials: A study from soft carbon to hard carbon. (September 2021) - Cheng, Dejian; Zhou, Xiuqing; Hu, Huanying; Li, Zhenghui; Chen, Jun; Miao, Lei; Ye, Xiaoji; Zhang, Haiyan
Abstract: Carbon materials are considered to be one of the most promising anodes for sodium ion batteries. However, the sodium storage mechanism of carbon anodes is still in dispute. In the current work, we prepared a series of carbon materials ranging from soft carbon to hard carbon, with well tailorable microcrystal structure and closed pores. By employing these carbons as anodes for sodium-ion batteries, it is interesting to find that the sodium storage in carbon materials follows an "intercalation/defect adsorption−closed pore filling" mechanism. That is, intercalation reaction/defect adsorption contributes to sloping region in the charge/discharge curves, while the plateau region is ascribed to closed pore filling. Furthermore, the systematical electrochemical study of soft carbon and hard carbon is implemented. The results show that, in comparison with soft carbon, hard carbon has large sodium storage capacity owing to the incorporation of plateau region; however, the plateau region presents slow reaction kinetics, leading to relatively inferior rate performance. Graphical abstract: Image 1